Application of Emergency Specialist Nursing Combined with Green Channel Mode in Patients with Limb Amputation - Zaiyun Qian; Min Wang; Tonglong Xu (Applied Bionics and Biomechanics)
Background. The treatment of limb amputation is always a challenge to emergency medical staff. The success of replantation of severed limbs requires not only emergency professional nursing measures but also rapid transport against time. We that found emergency specialist nursing combined with green channel mode can effectively improve the success rate of amputated limb replantation surgery. Methods. From September 2017 to August 2020, the medical records of 80 patients with severed limb replantation treated by the emergency department of our hospital were collected and divided into the control group and the experimental group. 36 patients in the control group were emergency patients treated from September 2017 to May 2019. These patients did not take appropriate emergency specialist nursing measures and opened green channels at that time; the other 44 patients were in the experimental group, for emergency patients treated from June 2019 to August 2020. These patients have received emergency specialist care and opened a green channel. We recorded the gender, age, preoperative examination time, and success rate of amputated limb replantation surgery of the two groups of patients. Results. The age of the patients in the control group was 41.17±8.00 years old, and the age of the patients in the experimental group was 41.07±7.31 years old (P>0.05). The preoperative examination time of the patients in the control group was 46.53±4.11 min, and the preoperative examination time of the patients in the experimental group was 40.34±5.85 min (P<0.05); the replantation success rate of the control group was 72.2%, and the replantation success rate of the experimental group was 81.8% (P<0.05). Conclusion. Standardized emergency specialist nursing measures combined with green channel mode can effectively shorten the preoperative examination time and help improve the success rate of amputated limb replantation surgery.